Burned-out testicular cancer - case report - Szarek, Mateusz; Stolarek, Kacper; Andrzejak, Alicja; Olszewski, Hubert (Quality in Sport, 2024)
Introduction and Purpose Germ cell tumors of the testis are the most common malignant tumors in young men aged 15-40, although their incidence in the male population is about 1-1.5%. 90-98% of all testicular tumors originate from germ cells. There has been an increase in the incidence of testicular tumors in recent years, suggesting the influence of both genetic and environmental factors. Testicular cancer, which accounts for about 5% of all urological cancers and mainly affects young men. Most of these cancers originate from germ cells, and cases of spontaneous tumor regression are extremely rare. Aim of the study We present the case of a 36-year-old man who was found to have a left testicular tumor with negative tumor markers during physical examination and testicular ultrasound. The tumor was surgically removed, and the patient was discharged home. Histopathological examination showed that the tumor had completely necrosed, and a CT scan showed no metastasis. Results and Future directions The phenomenon of testicular tumor “burnout” has been described since 1927, but it was only in 2016 that the WHO recognized it as a separate disease entity. Despite the rarity of this phenomenon, more and more cases are being reported in the literature, allowing for a better understanding of the underlying mechanisms. It is important to remember that the tumor can give a variable clinical picture and its symptoms are not necessarily related to the location of the tumor, but to its metastasis. Physical and ultrasound examinations are key to making a correct diagnosis. Histologic features such as scar formation, intravesicular calcification, lymphoplasmocytic infiltration and testicular atrophy can help diagnose germ cell tumor. The findings of this case demonstrate the need for diagnostic vigilance, especially in patients with equivocal tumor marker results but with clinical signs of testicular tumor.